The Importance of Mentorship Opportunities for Women in Academia: A Systematic Review - Zintle Ntshongwana (African Journal of Inter-Multidisciplinary Studies, 2024)
This paper aims to review the literature on the importance of mentoring in academia, specifically focusing on enhancing women's careers in academia. This study focuses on studies published between 2000-2023. Due to gender imbalance in academia, mentoring of early-career female academics has been recognised as instrumental in improving their aspirations. However, this tool is not receiving the recognition that it deserves, especially for women in academia. It further briefly discusses how mentoring is used as a resource to foster institutional change and decolonise entrenched academic promotion practices of paternalism. Radical feminist theory underpinned this study as this theoretical position helps explain the power inequalities that occur in higher education institutions (HEIs) and women’s communities and how these in turn inhibit the progress of women in academia. Furthermore, the African philosophy of Ubuntu is also used to explain how women can be supported in academia using indigenous African epistemology. A systematic review approach was used by searching for studies that focused on the importance of mentoring in academia. The findings of the review revealed numerous significant challenges that women in academia encounter. In addition, various benefits of mentoring were uncovered and discussed.